Effectiveness of Diflubenzuron in the control of houseflies - Rina Tilak; A.K. Verma; Urmila B. Wankhade (Journal of Vector Borne Diseases, 2010)
Background & objectives: Houseflies are one of the major pest problems worldwide. The currenthousefly control strategy in the country hinges on the use of Dichlorvos as a housefly larvicide andpyrethrum spray in kitchens/dining areas. The present study was undertaken to evaluate the newerhousefly control options in the wake of concerns about human toxicity of Dichlorvos and itscontinued use in public health.Methods: Efficacy of Diflubenzuron WP and granule formulations (chitin synthesis inhibitor) visà-vis Dichlorvos EC in the control of housefly was assessed in laboratory by adult emergenceinhibition after treatment and in field conditions by estimation of density post-application up tothree weeks using standard methods.Results: Dichlorvos EC and Diflubenzuron formulations (WP and granule) brought about 100%inhibition of adult emergence under laboratory conditions. However, in the field evaluation, effectivesuppression of housefly population was brought about by Dichlorvos and Diflubenzuron granuleformulation (though delayed).Conclusion: Dichlorvos EC and Diflubenzuron granule formulation are effective housefly larvicides.It is recommended that Diflubenzuron WP formulation be evaluated at a higher frequency toenhance its effectiveness and its use may be considered in conjunction with an initial suppressionof housefly adults with an adulticide, e.g. Cyphenothrin, etc.